2016
DOI: 10.1088/0022-3727/49/17/175003
|View full text |Cite
|
Sign up to set email alerts
|

The magneto-structural transition in Mn1−xFexCoGe

Abstract: Large refrigeration capacities, between 212(30) J kg-1 and 261(40) J kg-1 for a magnetic field change from 0 T to 5 T, were obtained in Mn1-xFexCoGe (x = 0.01, 0.02, 0.03 and 0.04) compounds. A partial magnetic phase diagram has been derived on the basis of magnetic transition and martensitic transformation temperatures determined from differential scanning calorimetry (200 K to 450 K), variable temperature x-ray diffraction (20 K to 310 K) and magnetisation measurements (5 K to 340 K; 0.01 T). Mn1-xFexCoGe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 50 publications
2
13
0
1
Order By: Relevance
“…we would assume a value of 3.67 µ B for Mn moment again using the assumption of a zero Co moment value. This inconsistency is the subject of continuing analysis . As expected, the main crystallographic phase of the Mn 0.98 Fe 0.02 CoGe sample at 365 K is hexagonal and paramagnetic (see Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…we would assume a value of 3.67 µ B for Mn moment again using the assumption of a zero Co moment value. This inconsistency is the subject of continuing analysis . As expected, the main crystallographic phase of the Mn 0.98 Fe 0.02 CoGe sample at 365 K is hexagonal and paramagnetic (see Fig.…”
Section: Resultsmentioning
confidence: 63%
“…b) indicates that Mn 0.98 Fe 0.02 CoGe adopts a ferromagnetic structure below T MS . As discussed fully elsewhere , all of the models for the space group Pnma were simulated and results show that the representation model Γ 3 (collinear ferromagnetic structure aligned along c ‐axis) gives the best refinement of the data. The initial neutron diffraction refinements show that the sample adopts a magnetic structure consisting of Mn moments aligned ferromagnetically along the c ‐axis, with a magnetic moment of 3.98(6) µ B .…”
Section: Resultsmentioning
confidence: 99%
“…4(a). Similar to other MnCoGe-based compounds [10,28], the relationship between the lattice parameters of the orthorhombic and hexagonal structures are: a orth ~ c hex , b orth ~ a hex , c orth /√3 ~ a hex and V orth /2 ~ V hex . In addition, a volume reduction by 4.0% (ΔV/V = (V orth /2 -V hex )/(V orth /2)) occurs from the low-temperature orthorhombic structure to the hightemperature hexagonal structure.…”
Section: Phase Evolutions and Magneto-structural Transitionmentioning
confidence: 69%
“…Compared with a model that considers that both the Mn and Co sublattices in the orthorhombic structure carry a magnetic moment, the model in which only the Mn sublattice carries a magnetic moment along the c orth -axis is found to be consistent with the results from the saturated magnetisation measurements presented in Section 3.4 (Table 3). This indicated that the magnetic moment in Mn(Co 0.96 Fe 0.04 )Ge mainly comes from the Mn sublattice and that magnetic moment on the Co sublattice is so small that it cannot be resolved by powder neutron diffraction, similar to the case of as-prepared (Mn 0.98 Fe 0.02 )CoGe [28]. Thus only the magnetic moment on the Mn sublattice in the orthorhombic phase was considered in the Rietveld refinement of the neutron diffraction patterns.…”
Section: Magnetic Structuresmentioning
confidence: 98%
“…元素化学替代: 元素替代法是最为常见、也是较容易 控制和调整相变温度的方法. 用Si [13] , Sn [14,15] , Al [16,17] , Fe [18,19] , Cr [20] , V [21] , Co [22] , Ti [23] , Cu [24][25][26] , Ni [27,28] , Zn [29] , Ga [30] , In [12] , Si [31] , Zr和Pd [32] 等元素替代过渡金属(Mn, Co)或主族元素(Ge)都被证明是有效的. Liu等人 [33] [34] 及Fe-Ga磁致伸缩材料 [35]…”
Section: 度以使磁相变和结构相变耦合起来是Mm′x材料研究 的重要内容之一unclassified